Knowledge and Preventive Practice Regarding Hepatitis B Among The Nurses in Dhaka Medical College Hospital - Khan, Nirmeen Rifat; Riya, Sayeda; Islam, Mohammad Shohidul; Majeed, Hisham Abdul (Journal of Dhaka Medical College, 2017)
This was a descriptive cross-sectional study conducted with an aim to assess the level of knowledge and preventive practice regarding hepatitis B among the nurses in Dhaka Medical College Hospital. The study was conducted from January 2015 to June 2015. Total sample was 207 and purposive sampling technique was followed for data collection, which was done by face to face interview. The data were collected on a structured questionnaire and analyzed by SPSS. Out of 207 respondents, majority (54.1%) were found in the age group of 18 to 30 years, where mean age was 33 + 0.2 years. Among them female (83.5%) outnumbered the male (16.4%). Most of them (81.2%) were Muslim. Majority (49.8%) were educated up to HSC level and half of them (51.7%) were married. Majority(45.4%) had family income > 20,000 taka. Most of them (91.8%) had good knowledge that virus was the causative agent of hepatitis B and 84.5% understood infected blood transfusion as common means of disease transmission. About 83.1% had the knowledge about other routes of transmission. Nearly half (51.7%) were not aware of being at risk of infected by HBV but more than half (56.5%) received vaccination for HBV. Most of them (85%) stated that hepatitis B had complications. Mean knowledge score was 8.28 + 2.9, while 80.7% had good level of knowledge, only 19.3% had poor knowledge. Again, mean preventive practice score was 4.78 + 1.3, while 87.4% had good level of preventive practice and 12.6% had poor preventive practice. Here mean practice of prevention was significantly associated with level of knowledge of respondents (P<0.001). In the study overall knowledge and practice was found to be satisfactory. Most of the nursing staffs were at risk of hepatitis B. So appropriate educational and health promotion programs can increase these knowledge & practice further. J Dhaka Medical College, Vol. 26, No.1, April, 2017, Page 36-42